Exploring the Antioxidant Potential of a Polyherbal Combination: A Comprehensive in vitro Study - Aalam, Athar; Rastogi, Vaibhav; Porwal, Mayur (International Journal of Pharmaceutical Investigation, 2025)
Background The objective of this research was to explore the antioxidant potential of the three different medicinal plant extracts namely Curcuma longa, Acacia catechu and Allium cepa along with their combination (polyherbal) as well as to evaluate their phytochemicals, physical parameters, quantitative analysis of flavonoids, phenolic contents. Materials and Methods The three plants’ ethanolic extracts were collected using the soxhlet apparatus. The phytochemicals of the plant extracts were analyzed using different analytical reagents. Physical parameters such as extractive value, Loss on Drying (LOD), and ash values have been studied. The Folin-Ciocalteu phenol reagent was used to assess the phenolic content, and the aluminium chloride colorimetric technique was used to calculate the flavonoid level. The antioxidant activity of the individual plant extract and the polyherbal extracts (10 µL each extract) was determined using the DPPH, ABTS, hydroxy free radical scavenging assay, CUPRAC, FRAP, and superoxide anion radical scavenging assay. Results The phytochemical tests revealed the common presence of flavonoids, tannins, and glycosides in C. longa, A. catechu and A. cepa. The extractive value was calculated as 24.90 g, 6.93 g, and 30.71 g, for C. longa, A. catechu, and A. cepa respectively. The total ash (%w/w), acid-insoluble ash (%w/w), and water-soluble ash (%w/w) values for C. longa were 13.21, 1, and 4.13, respectively, for A. cepa was 2.59, 0.28, and 1.09, respectively, and for A. catechu was 12.6, 1.63, and 6.25, respectively. LOD (%w/w) for C. longa, A. cepa, and A. catechu was found to be 4.09, 10.59, and 7.23, respectively. The total phenolics content was found to be 56.08±0.23 mg GAE/g, 39.7±0.20 mg GAE/g, and 16.0±0.2 mg GAE/g in C. longa, A. catechu, and A. cepa, respectively. Total flavonoid content was calculated as 19.1±0.3 mg QE/g, 9.12±0.3 mg QE/g, and 53.89±0.30 mg QE/g in C. longa, A. catechu, and A. cepa, respectively. All the extracts including the polyherbal combination showed significant antioxidant activity by assessing their IC50 value. Conclusion The superoxide anion radical scavenging assay verifies the robust efficacy of the polyherbal extract and proposes it as a specific antioxidant drug against disorders associated with excessive superoxide radical production like wound, atherosclerosis, amyotrophic lateral sclerosis, cancer progression, rheumatoid arthritis, accelerated aging, etc.
Keywords: Polyherbal combination; Phytochemical analysis; Antioxidant activity; DPPH; ABTS; Hydroxy free radical scavenging assay; CUPRAC; FRAP; Superoxide anion radical scavenging assay